The Effect of Utilizing Productive Zakat, Infaq, Sedekah (ZIS) in Improving Mustahik’s Welfare at Baitul Mal Aceh - Muhammad Haris Riyaldi; Salma Salma (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
This study aims to compare the welfare of mustahik who are assisted by business capital loans and work equipment through the use of productive zis in Baitul Mal Aceh. This study also analyzes the effect of the dimensions of productive Zakat, Infaq, Alms (ZIS) utilization on the welfare of mustahik. This research is a field research using quantitative methods. The population in this study were mustahik who received productive ZIS utilization in the form of qardhul hasan and work tools in the cities of Banda Aceh and Aceh Besar. The data collection instrument used a questionnaire with a sample of 86 respondents who were selected using simple random sampling. Data were analyzed using independent samples t-test to compare the level of welfare of mustahik between the two models of productive ZIS utilization. The data were also analyzed using multiple regression to examine the effect of the dimensions of empowerment, namely socialization, coaching and mentoring on the welfare of mustahik. The results showed that there was no significant difference between the welfare of mustahik who were empowered with the qardhul hasan model compared to the welfare of mustahik who were empowered by the work tool model. Socialization, coaching and mentoring have a significant effect on the welfare of the mustahik Baitul Mal Aceh, either partially or simultaneously. It is hoped that Baitul Mal Aceh will continue the productive ZIS utilization program and increase socialization, guidance and assistance for the successful development of mustahik businesses.